Analgesic potential of rosemary essential oil in acetic acid induced writhing test on NMRI-Haan mice - Milanović, Isidora; Rašković, Aleksandar; Stilinović, Nebojša; Vukmirović, Saša (Archives of Pharmacy, 2022)
The analgesic and anti-inflammatory effects of rosemary essential oil (REO), its components, and other essential oils with similar content (1,8-cineole, camphor and α-pinene) have been studied in animal models, with administration of high doses. The aim of our study was to investigate analgesic potential of rosemary essential oil when used in smaller doses. In this study REO was orally administered at doses of 10 and 20 mg/kg bw/day for seven days. Painful infliction was induced by administration of 1% acetic acid intraperitoneally (10 ml/kg bw), 10 minutes after the last REO dose. Writhes counting started 5 minutes later. During the first period (5 – 25 minutes), pretreatment with REO (10 and 20 mg/kg bw/day), resulted in statistically significant (dose-dependent) reduction in the number of writhes (p˂0.05), compared to the control group pretreated with saline. During the second counting period (25-45 minutes), statistically significant difference between the control and experimental groups was not detected. In our study, the application of REO caused a significant antinociceptive effect. Rosemary essential oil significantly reduces visceral pain caused by the irritation with acetic acid after a seven-day oral treatment in doses of 10 mg/kg bw and 20 mg/kg bw.